Assessment of physicochemical conditions and plankton populations of the river Padma, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was conducted to investigate the physicochemical and biological aspects of the river Padma in three sampling stations viz Mawa, Godagari and Paksi from January 2014 to December 2014. Ten physical and nine chemical parameters of water and plankton community both phytoplankton and zooplankton of this aforesaid area were studied. Physicochemical parameters of water such as temperature, pH, hardness, alkalinity, dissolve oxygen (DO), free carbon dioxide (CO2), total dissolve solids (TDS), turbidity, biological oxygen demand (BOD) and chemical oxygen demand (COD) were studied. Maximum water depth 23.9±6.5 ft was recorded from Paksi and lowest water depth (19.7±6.3 ft) was recorded in Godagari. The highest air temperature was found 32.5±8.90C in Paksi and lowest temperature was found 28.3±3.90C in Godagari. Water temperature was found lowest (25.7±4.10C)   in Godagari and highest (29.3±7.90C) in Paksi. Transparency was found lowest in Godagari 36.4±16.4 cm and highest 45.9±20.5 cm in Paksi. Conductivity was found highest in 390.2±411 (µs/cm) in Godagari. Turbidity was found lowest 16.5±36.3 in Paksi. TDS was found highest 190.4±196.9 mg/l in Godagari. Dissolve oxygen content in Mawa was found lowest 6.71±1.1 mg/l. pH was ranging from 8.0±2.4 in Mawa to 8.2±0.2 in Godagari among the three sampling spots of Padma river. Total alkalinity was found lowest 98.2±36.7 mg/l in Paksi. Total hardness was found lowest 83.4±45.9 mg/l in Godagari. BOD (B) was found highest 6.2±1.6 mg/l in Mawa. COD was found lowest 13.1±8.6 mg/l in Paksi. Total plankton density was found 2100±695.4 (Nos. /l) in Mawa, 2350±670.2 (Nos./l) in Godagari and 2280±710.5 (Nos./l) in paksi respectively. Total sixty genera under six classes of phytoplankton were observed and twenty two genera of zooplankton under four families were identified. Chlorophyceae, Bacillariophyceae, Cyanophyceae, Xanthophyceae, Euglenophyceae and Dinophyceae were the major groups of phytoplankton and Rotifera, Copepod and Cladocera were the major groups of zooplankton during the study period. The mean contribution of phytoplankton was more than 91.33% in all three rivers and zooplankton contributed the rest.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (1), 86-94